Intravascular lithotripsy to treat an underexpanded coronary stent: 4‐Month angiographic and OCT follow‐up. Issue 6 (20th January 2020) - Alawami, Mohammed; Thirunavukarasu, Sharmaine; Ahmed, Javed; El‐Omar, Magdi
Abstract: We report the case of a 79‐year‐old man with stable angina who underwent percutaneous coronary intervention to a severe and calcified left circumflex lesion. Despite extensive preparation of the lesion with high‐pressure balloon predilatation and rotablation, the implanted stent was grossly underexpanded and failed to respond to high‐pressure balloon postdilatation. The patient was readmitted 6 weeks later for intravascular lithotripsy that resulted in excellent stent expansion. Coronary angiography with optical coherence tomography 4 months later revealed sustained acute lumen gain with no evidence of stent recoil or in‐stent restenosis.